Makna Uang Dalam Konstruksi Kesadaran Etis Akuntan - Ludigdo, Unti (TEMA, 2008)
This paper shows the research result in accounting ethics discipline. The research objective is to explore and show the expression of a public accountant's ethical consciousness. By using ethnomethodology, this research finds that ethical consciousness is individual phenomena which its born and growth are affected by many causes. In this context, Mantra (research informan) was bom as the child of a farmer and grew in a farm culture that has different ethical consciousness with the other professional accountants. For him, helping his clients and maintaining longly relationship with his clients are virtue in his professional life. Money is important but it isn’t the most important factor and it isn’t of all. If in the workplace money is taken in the top of all, in the longtime it has many implication to his life. Mantra doesn’t want this to happen. Mantra’s discurcive and practical consciousness developed through a longlife process, where Mantra always wants to learn from his past and effort to strengthen his emotional and spiritual power. Keywords: Ethical Consciousness, Accountant, Ethnomethodology.